The Effect of Peer Education on Learning Vaccination Principles among Nursing Students of Shiraz University of Medical Sciences - Malihe Abootalebi; Naval Heydari; Fatemeh vizeshfar; Maryam Paran (Zanjan University of Medical Sciences and Health Services, 2019)
Background: Peer education is one of the active teaching methods and is rarely used in clinical settings, especially in nursing. Objectives: This study aimed to investigate the effects of Peer Assisted Learning (PAL) on learning the principles of vaccination in nursing students. Methods: This quasi-experimental study was performed on 79 (intervention group n=43, control group n=36) nursing students. In the intervention group, seven peer instructors taught the principles of vaccination in two one-hour sessions to other students. The control group received routine education. Data were collected using a questionnaire. Results: The findings showed that among the students, 43% (n=34) were male and 57% (n=45) were female participants. The difference between the intervention and control groups was significant after the intervention (P<0.001). Besides, the comparison of the average score of the checklist between the two groups showed significant differences (P<0.001). Conclusion: The results of this study showed the positive impact of PAL on clinical education as well as its reliability and benefits for nursing students.